2004
DOI: 10.2166/wst.2004.0025
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of opportunistic pathogens in municipal drinking water under different supply and treatment regimes

Abstract: Changing regulations to lower disinfectant byproducts in drinking water is forcing utilities to switch disinfection from chlorine to monochloramine. It is generally unknown whether this will impact positively or negatively on the microbiological quality of drinking water. A utility in Florida, using water with relatively high organic carbon levels from deep wells in several wellfields, made the decision to change its disinfection regime from chlorine to chloramine in order to meet the new regulations. To asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 0 publications
6
82
5
Order By: Relevance
“…NTM were observed in drinking water by others using cultivation methods, but the numbers of positive samples ranged from 15% to 83% (8,(38)(39)(40)(41)(42)(43), lower than the 100% positive drinking water samples observed with qPCR in our study. A recent study demonstrated that cultivation methods give an underestimation of NTM in drinking water compared to estimation with qPCR (40).…”
Section: Discussioncontrasting
confidence: 86%
“…NTM were observed in drinking water by others using cultivation methods, but the numbers of positive samples ranged from 15% to 83% (8,(38)(39)(40)(41)(42)(43), lower than the 100% positive drinking water samples observed with qPCR in our study. A recent study demonstrated that cultivation methods give an underestimation of NTM in drinking water compared to estimation with qPCR (40).…”
Section: Discussioncontrasting
confidence: 86%
“…Regardless of the precise nature of this association, it implies that there might be source-specific factors that predict colonization of buildings by Legionella and that these factors can be overcome by MC. Despite the positive findings of our study, Pinellas County Utilities, in cooperation with other investigators, observed several negative and potentially detrimental outcomes following the conversion to MC (16). The proportion of buildings that were colonized by mycobacteria increased from 19.1% during the CL phase to 42.2% during the MC phase.…”
Section: Discussioncontrasting
confidence: 81%
“…are more susceptible to residual chlorine in potable water. Although intracellular growth within amoeba was frequently reported essential for their resistance to chlorination stress and persistence in DSs, some studies showed that residual chlorine could exert negative impacts on the growth of Legionella spp., and in some cases Legionella bacteria outnumbered mycobacteria in DS biofilms under low disinfection levels but different in turn under heavy disinfection stress (Pryor et al, 2004;van der Kooij et al, 2005). Considering the consumption of chlorine during the corrosion process, low-chlorine or even chlorine-free niches might extensively exist in the cast iron biofilm, resulting in the higher occurrence of Legionella species.…”
Section: Bacterial Communitiesmentioning
confidence: 99%